Cytotoxic Agents in the Minor Alkaloid Groups of the Amaryllidaceae - Nair, Jerald J.; van Staden, Johannes (Planta Medica, 2021)
Over 600 alkaloids have to date been identified in the plant family Amaryllidaceae. These have been arranged into as many as 15 different groups based on their characteristic structural features. The vast majority of studies on the biological properties of Amaryllidaceae alkaloids have probed their anticancer potential. While most efforts have focused on the major alkaloid groups, the volume and diversity afforded by the minor alkaloid groups have promoted their usefulness as targets for cancer cell line screening purposes. This survey is an in-depth review of such activities described for around 90 representatives from 10 minor alkaloid groups of the Amaryllidaceae. These have been evaluated against over 60 cell lines categorized into 18 different types of cancer. The montanine and cripowellin groups were identified as the most potent, with some in the latter demonstrating low nanomolar level antiproliferative activities. Despite their challenging molecular architectures, the minor alkaloid groups have allowed for facile adjustments to be made to their structures, thereby altering the size, geometry, and electronics of the targets available for structure-activity relationship studies. Nevertheless, it was seen with a regular frequency that the parent alkaloids were better cytotoxic agents than the corresponding semisynthetic derivatives. There has also been significant interest in how the minor alkaloid groups manifest their effects in cancer cells. Among the various targets and pathways in which they were seen to mediate, their ability to induce apoptosis in cancer cells is most appealing.
Keywords: Amaryllidaceae; antiproliferative; cancer; cytotoxic; isoquinoline alkaloid